The Psychometric properities of the online teaching competencies scale among faculty members at Umm Al-Qura University - Hafiz, Eptehal Zakaria (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the psychometric characteristics of the e-teaching competencies scale among faculty members at Umm Al-Qura University, and to identify the level of their e-teaching competencies. (515) members of the teaching staff at Umm Al-Qura University, and the data were analyzed using descriptive statistics, exploratory factor analysis and independent t-test in the SPSS program (28). The results concluded: that the overall stability of the scale (0.097), and the results of the exploratory factor analysis concluded that (47) phrases are saturated in seven factors, namely (technology, continuous formative assessment, social personality, test management, teaching and teaching strategies, planning and design, interaction and communication with The results showed that the degree to which UQU faculty members possessed the competencies of electronic teaching was largely available, and the results showed that there were statistically significant differences at the level (0.05) in the averages of the electronic teaching competencies, namely learning strategies, interaction and communication with students between the practical group and the colleges. Theory for the benefit of faculty members in practical colleges. The study recommends the development of e-teaching skills among faculty members, especially in theoretical colleges, and conducting training courses for faculty members to keep pace with technological development and benefit from them in developing teaching performance.
Keywords: psychometric properities; online teaching competenies; exploratory factor analysis